ICAM-1 expression in renal disease. Issue 10 (October 1992) - Chow, J; Hartley, R B; Jagger, C; Dilly, S A
Abstract : AIM: To determine the role of intercellular adhesion molecule-1 (ICAM-1) in immune mediated damage in glomerulonephritis, and whether its expression correlates with disease activity. METHODS: Fifty three renal biopsy specimens from a range of non-immune renal disease and low grade and high grade glomerulonephritides were stained with ICAM-1. Positivity was assessed in the tubules. Tubular damage and accompanying interstitial inflammation were also noted. The ICAM-1 positivity in damaged and undamaged tubules was correlated with the three groups of renal disease. RESULTS: ICAM-1 positivity in undamaged tubules was observed in glomerulonephritis, and this showed a strong correlation with disease activity. In contrast, ICAM-1 positivity on damaged tubules correlated with evidence of chronic tubular damage, and was seen in a large proportion of cases, regardless of the underlying disease. There was no correlation between ICAM-1 positivity and a local lymphocytic infiltrate. CONCLUSION: ICAM-1 probably has an important role in the pathogenesis of glomerulonephritis. Its expression may be secondary to cytokines released by cells participating in the glomerular damage. As these cytokines also influence tubule function, tubular ICAM-1 expression may be a marker of the extent of tubular disturbance in glomerulonephritis.